CHINESE CAPITAL GOES GLOBAL: THE BELT AND ROAD INITIATIVE AND BEYOND - Shi, Weiyi; Ye, Min (Journal of East Asian studies, 2021)
The Belt and Road Initiative (BRI), and China's state-led model for economic globalization more generally, have attracted controversy: Are state-led overseas investment and lending driven by strategic motives or market rationale? How have the recipient economies reacted to the influx of Chinese capital? This special issue sheds light on these questions by first outlining the fragmented state system driving the BRI, a system featuring both Beijing's strategic logic at the top and market considerations in policy implementation. The role of the state is unpacked further in China's globalizing coal industry and in the growth of Chinese industry export to BRI countries. Finally, the issue explores the mechanisms behind public backlash and political pushback facing China in Zambia and Australia. As the COVID-19 pandemic continues to shift China's relationship with the world, this special issue contributes to a more nuanced understanding of the modus operandi of Chinese capital going global.